2004
DOI: 10.1038/sj.bjc.6602068
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of childhood leukaemia in the vicinity of nuclear sites in France, 1990–1998

Abstract: . There was no evidence of a trend in standardised incidence ratio with distance from the sites for all children or for any of the three age groups studied. Similar results were obtained when the start-up year of the electricity-generating nuclear sites and their electric nuclear power were taken into account. No evidence was found of a generally increased risk of childhood leukaemia around the 29 French nuclear sites under study during 1990 -1998.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…"Our study shows no evidence of a generally increased risk of childhood leukaemia within 20km of the 29 nuclear sites under study" (White Koning et al 2004). …”
Section: Empirical Studies Of Cancer Incidence Around Nuclear Power Pcontrasting
confidence: 52%
“…"Our study shows no evidence of a generally increased risk of childhood leukaemia within 20km of the 29 nuclear sites under study" (White Koning et al 2004). …”
Section: Empirical Studies Of Cancer Incidence Around Nuclear Power Pcontrasting
confidence: 52%
“…A previous study of the incidence of leukaemia around all French nuclear installations found neither evidence of an overall increased incidence of childhood leukaemia in the vicinity of the 29 main nuclear installations during 1990 -1998 nor a trend in standardised incidence ratio (SIR) with increasing distance from the sites for all children under 15 years of age (White-Koning et al, 2004). Compared to this study, the present study includes three additional years of observation (1990 -2001).…”
mentioning
confidence: 72%
“…The use of residential proximity as surrogate exposure assumes an isotropic and isotonic decrease of exposure with distance. However, although commonly used [28,29], this approach ignores among others the impact of wind direction and is therefore radio-ecologically not plausible [30]. The same holds true when using prevailing wind directions as surrogate of exposure, by which the impact of distance is ignored.…”
Section: Discussionmentioning
confidence: 99%